1H-NMR-Based Metabolomic Study of Potato Cultivars, Markies and Fianna, Exposed to Different Water Regimes - Mdlalose, Samukelisiwe P.; Raletsena, Maropeng; Ntushelo, Khayalethu; Bodede, Olusola; Modise, David M. (Frontiers in Sustainable Food Systems, 2022)
This study investigated the effects of varying soil moisture conditions (through either flooding, drought, or provision of a moderate water supply) on the metabolomic profile of two potato cultivars, Markies and Fianna. Representative tubers of the treated plants were collected 91 days after planting. The samples were freeze-dried, and ground to a fine powder in liquid nitrogen. The fine powder of the tuber samples was analysed by nuclear magnetic resonance spectroscopy (NMR) to identify their metabolomic profiles. The NMR data was analysed using principal component analysis and orthogonal partial least square discriminant analysis to identify any variations between the treatments. In both models, plants exposed to drought clearly separated from the plants that received either excess or moderate water. The potato tubers that experienced drought and flood treatments had the highest quantities of aspartic acid, asparagine, and isoleucine. Furthermore, the potatoes exposed to either drought or flood also had higher levels of valine and leucine (which are essential for plant defence and resistance against plant pathogens). Potato plants have the ability to respond metabolically to varying soil moisture stress.